Investigation for Carbonation Mechanism of Tobermorite 9 Å: A Combination of DFT and Ab Initio Molecular Dynamics Study. Issue 1 (26th November 2022) - Liu, Xiaotong; Bai, Xiaolin; Zhong, Wei; Deng, Xiangsheng; Liang, Tianshui
Abstract: Hydrated calcium silicate carbonation leads to reinforcement corrosion and strength reduction. The carbonation mechanism of Tobermorite 9 Å is researched by density functional theory calculation and ab initio molecular dynamics (AIMD). Results show that the lowest surface energy of Tobermorite 9 Å (001) slab is (001) surface. The bridge position of Ca1 ─Ca5 atom is the most stable adsorption position for carbon dioxide molecules. In terms of charge density difference, the results show that the Ca atom loses electrons and the O atom gains electrons. In terms of partial density of states, the results show that there are unobvious hybridization orbitals between Ca d‐ and O p‐orbitals, which leads to the formation of a very weak Ca─O bond. In terms of AIMD simulation at the temperature of 1073 K, the results show that the carbon dioxide gradually develops from adsorption to desorption on the Tobermorite 9 Å (001) surface. These findings provide profound views in understanding the carbonation of hydrated calcium silicate. Abstract : The lowest surface energy of Tobermorite 9 Å (001) slab is (001) surface. The bridge position of Ca1 ─Ca5 atom is the most stable adsorption position for CO2 . In the charge density difference, the Ca atom loses electrons and the O atom gains electrons. In the ab initio molecular dynamics, the CO2 gradually develops from adsorption to desorption at 1073 K.